PRECONDITIONS FOR EARLY AND LATE INTRAVENTRICULAR HEMORRHAGES IN PRETERM VERY LOW BIRTH WEIGHT INFANTS - Dobryanskyy, D.O.; Horinets, I.O.; Menshykova, A.O.; Sodomora, O.O.; Matsyura, O.I. (World of Medicine and Biology, 2020)
The risk factors for early and late intraventricular hemorrhages (IVH) in very preterm newborns were investigated in a cohort study. One hundred eleven infants with a mean gestation age of 29.59±2.59 wks. were under observation. The risk factors connected to the development of early and late hemorrhages were different. Opposite to the early IVH, development of the late hemorrhages was neither dependent on birth weight and gestation age, nor on infectious pathology of perinatal period. The relevant risk was determined by infant’s condition at birth and arterial hypotension that developed within the first 24 hrs. of newborn’s hospitalization. Development of severe respiratory distress syndrome (RDS) was reliably connected with IVH independently on infant’s age. According to the results of logistic regression analysis, the risk of early IVH was significantly associated with RDS severity (odds ratio [OR]: 6.05; 95% confidence interval [CI]: 1.35–27.17), and the probability of late IVH was significantly influenced by arterial hypotension within the first 24 hrs. of hospitalization (OR: 16.6; 95% CI: 2.69–102.43).
Keywords: intraventricular hemorrhages; age of occurrence; risk factors; prevention; very preterm infants